Postnatal Prognosis of Fetal Noncompaction Is Uncertain In Sibs Carrying a PKP2 Deletion - Finsterer, MD, PhD, Josef; Zarrouk-Mahjoub, PhD, Sinda (Journal of Medical Biomedical and Applied Sciences, 2018)
See the pdf